Perceptions Of Coaches And Athletes In Using Android-Based Match Statistics Applications At National Potential Young Athlete Training Centers (SLOMPN) - Muchamad Arif Al Ardha; Kolektus Oky Ristanto; Rizky Muhammad Sidik; Muhammad Kharis Fajar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The study conducted at the National Potential Young Athletes Training Center (SLOMPN) of Unesa provides a crucial perspective on the use of an Android-based match statistics application. The research aims to optimize athletes' potential through the Long Term Athlete Development (LTAD) approach, integrating knowledge of athlete development with the application of technology in training. The survey results from 5 coaches indicate that the application aids in planning training, understanding application features, and assessing athlete development with positively skewed average scores. However, there is room for improvement, especially in terms of comfort during matches and communication with athletes. Meanwhile, 18 athletes showed positive acceptance of the application by rating its ease of use and impact on performance enhancement highly. Nevertheless, there is a need for improvement in injury recovery features and data security. This study underscores the importance of continuous collaboration between application developers and users to enhance the effectiveness of technology in sports training.